Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Sunini Huyền

Y=\(1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2012}}\)

Tính tổng

Hiiiii~
30 tháng 4 2017 lúc 10:27

Có:

\(Y=1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2012}}\)

\(\Rightarrow2Y=2+1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2011}}\)

Lấy 2Y-Y, ta được:

\(2Y-Y=\left(2+1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2011}}\right)-\left(1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2012}}\right)\)

\(2Y-Y=2+1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2011}}-1-\dfrac{1}{2}-\dfrac{1}{2^2}-\dfrac{1}{2^3}-...-\dfrac{1}{2^{2012}}\)\(2Y-Y=2+\left(1+\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2011}}-1-\dfrac{1}{2}-\dfrac{1}{2^2}-\dfrac{1}{2^3}-...-\dfrac{1}{2^{2011}}\right)-\dfrac{1}{2^{2012}}\)

\(2Y-Y=2+\left(-\dfrac{1}{2^{2012}}\right)=2-\dfrac{1}{2^{2012}}\)

Hay \(Y=2-\dfrac{1}{2^{2012}}=\dfrac{2^{2013}-1}{2^{2012}}\)

Chúc bạn học tốt!ok